Antiphospholipid antibodies during acute COVID-19 are not associated with long COVID: findings from a retrospective cohort study - Arcani, Robin; Brodovitch, Alexandre; Heim, Xavier; Mège, Jean-Louis; Bardin, Nathalie (Frontiers in Immunology, 2025)
IntroductionLong COVID is a public health issue with complex pathophysiology, potentially involving immunoinflammatory and prothrombotic mechanisms. Antiphospholipid antibodies (aPL) have been observed in acute COVID-19 and speculated to contribute to long COVID development. Our goal was to determine if the presence of aPL was associated with the progression towards long COVID.MethodsWe retrospectively analyzed all adult patients screened for aPL during acute COVID-19 in our institution between April 2020 and April 2022. Only patients with at least one follow-up ≥3 months post-infection were included.ResultsAmong 114 patients (median age 64.0 years, 44.7% female), 19 (16.7%) developed long COVID. Those with long COVID were younger and more frequently admitted to ICU than those who recovered. However, aPL positivity did not differ significantly between patients with and without long COVID (63.2% vs. 66.3%, p = 0.79).ConclusionOur findings suggest no association between aPL and the development of long COVID. Prior associations may reflect confounding factors such as ICU admission.